The effects of increasing the minimum wage on prices: Analyzing the incidence of policy design and context - Daniel MacDonald; Eric Andrews Nilsson (W.E. Upjohn Institute for Employment Research, 2016)
We analyze the price pass-through effect of the minimum wage and use the results to provide insight into the competitive structure of low-wage labor markets. Using monthly price series, we find that the pass-through effect is entirely concentrated on the month that the minimum wage change goes into effect, and is much smaller than what the canonical literature has found. We then discuss why our results differ from that literature, noting the impact of series interpolation in generating most of the previous results. We then use the variation in the size of the minimum wage change to evaluate the competitive nature of low-wage labor markets. Finally, we exploit the rich variation in minimum wage policy of the last 10-15 years - including the rise of state and city-level minimum wage changes and the increased use of indexation - to investigate how the extent of price pass-through varies by policy context. This paper contributes to the literature by clarifying our understanding of the dynamics and magnitude of the pass-through effect and enriching the discussion of how different policies may shape the effect that minimum wage hikes have on prices.
Keywords: J3; J48; J11; 330; Minimum wage; pass-through effect; monopsony; public policy